2019
DOI: 10.1002/epi4.12344
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid and benzodiazepine combination therapy reduces status epilepticus and long‐term effects of whole‐body sarin exposure in rats

Abstract: Objective Our objective was to evaluate the protective efficacy of the neurosteroid pregnanolone (3α‐hydroxy‐5β pregnan‐20‐one), a GABA A receptor‐positive allosteric modulator, as an adjunct to benzodiazepine therapy against the chemical warfare nerve agent (CWNA) sarin (GB), using whole‐body exposure, an operationally relevant route of exposure to volatile GB. Methods Rats implanted with telemetry transmitters for the continuous measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Neurosteroids, such as allopregnanolone, are modulators of the major inhibitory GABAA receptor (reviewed in Ref. 42 ), as well as anticonvulsive properties, 43,44 and these effects may contribute to the increased protection against GD lethality that we observed in the female Es1 −/− mice in estrus. Further research on species differences in the impact of sex on the toxic outcome of CWNA exposure may be warranted.…”
Section: Discussionmentioning
confidence: 93%
“…Neurosteroids, such as allopregnanolone, are modulators of the major inhibitory GABAA receptor (reviewed in Ref. 42 ), as well as anticonvulsive properties, 43,44 and these effects may contribute to the increased protection against GD lethality that we observed in the female Es1 −/− mice in estrus. Further research on species differences in the impact of sex on the toxic outcome of CWNA exposure may be warranted.…”
Section: Discussionmentioning
confidence: 93%
“…Regardless of the OP triggering seizures, prolonged SE induced by DFP, soman, or sarin has been associated with important neuronal loss in the hippocampus and other brain regions. 4,15,16 Elevated delta activity has been suggested to predict neuronal damage in a soman-induced poisoning model. 17 In our study, power spectra analysis of animals experiencing SE showed us that, as opposed to all other studied frequencies that were elevated during SE, only delta frequencies remained increased in the 24-hour recording period.…”
Section: Discussionmentioning
confidence: 99%
“…Even when seizures seem to stop by the administration of diazepam at 1 or 2 h after GD exposure, the intermittent return of seizures is observed in rats so that the overall duration of seizures in the first 24 h after the toxic insult is similar to that of animals that did not receive any anti-seizure treatment [ 23 ]. Midazolam, recently approved for the treatment of acute repetitive seizures, increases survival in GD-exposed rats and Es1-/- mice but does not prevent the development of spontaneous recurrent seizures (SRS) or brain pathology when treatment is delayed [ 13 , 18 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%